Enquête exploratoire sur le recueil de la variable linguistique dans les données administratives des hôpitaux de la région du RLISS-Champlain - Chomienne, Marie-Hélène; LeClerc, Chantale; Schnarch, Brian; Bouchard, Louise; McKay, Martine; Farmanova, Elina (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, Réseau local d’intégration des services de santé de Champlain, 2011)

La santé des francophones en situation minoritaire : un urgent besoin de plus d’information pour offrir de meilleurs services - Consortium national de formation en santé; Société Santé en français (La santé des francophones en situation minoritaire : un urgent besoin de plus d’information pour offrir de meilleurs services, 2010)

Qui sont les francophones ? Analyse des définitions selon les variables du recensement. Mise à jour : recensement de 2011 - Guignard-Noël, Josée; Forgues, Éric; Landry, Rodrigue (Institut canadien de recherche sur les minorités linguistiques, 2014)

Statistics Canada data sources on official-language minorities (n°91-549-X-n°2) - Lafrenière, Sylvie (Statistics Canada, 2013)

À l’intersection des définitions de langues : portrait des communautés linguistiques au Québec et dans les réseaux territoriaux de services en 2016. La langue, déterminant de l'état de santé et de la qualité des services - Lussier, Marie-Hélène; Tu, Mai Thanh; Blaser, Christine (Institut national de santé publique du Québec, 2019)

At the intersection of language definitions: A portrait of linguistic communities in Québec and its territorial service networks in 2016. Language as determinant of health and quality of services - Lussier, Marie-Hélène; Tu, Mai Thanh; Blaser, Christine (Institut national de santé publique du Québec, 2019)

Methodological issues in analysing small populations using CCHS cycles based on the official language minority studies - Makvandi, Ewa; Bouchard, Louise; Bergeron, Pierre-Jerôme; Sedigh, Golnaz (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Statistical analyses for small populations or small domains of interest can be challenging. To obtain reliable estimates, only very large surveys such as the Canadian Community Health Survey can be considered. However, despite its good geographical and temporal coverage, the analysis of small populations in smaller regions (e.g., health regions) and in regards to specific health issues remains challenging. We will look at the methodological issues in analysis of small populations in relation to sampling and non-sampling survey errors that affect the precision and accuracy of the estimates. Francophone minorities in Canada will be used to illustrate the issues throughout the paper.

Comparison of sampling methods for hard-to-reach Francophone populations: Yield and adequacy of advertisement and respondent-driven sampling - Ngwakongnwi, Emmanuel; King-Shier, athryn. M.; Hemmelgarn, Brenda. R.; Musto, Richard; Quan, Hude (Open medicine, 2014)
Francophones who live outside the primarily French-speaking province of Quebec, Canada, risk being excluded from research by lack of a sampling frame. We examined the adequacy of random sampling, advertising, and respondent-driven sampling for recruitment of francophones for survey research. Methods: We recruited francophones residing in the city of Calgary, Alberta, through advertising and respondentdriven sampling. These 2 samples were then compared with a random subsample of Calgary francophones derived from the 2006 Canadian Community Health Survey (CCHS). We assessed the effectiveness of advertising and respondent-driven sampling in relation to the CCHS sample by comparing demographic characteristics and selected items from the CCHS (specifically self-reported general health status, perceived weight, and having a family doctor). Results: We recruited 120 francophones through advertising and 145 through respondent-driven sampling; the random sample from the CCHS consisted of 259 records. The samples derived from advertising and respondentdriven sampling differed from the CCHS in terms of age (mean ages 41.0, 37.6, and 42.5 years, respectively), sex (proportion of males 26.1%, 40.6%, and 56.6%, respectively), education (college or higher 86.7% , 77.9% , and 59.1%, respectively), place of birth (immigrants accounting for 45.8%, 55.2%, and 3.7%, respectively), and not having a regular medical doctor (16.7%, 34.5%, and 16.6%, respectively). Differences were not tested statistically because of limitations on the analysis of CCHS data imposed by Statistics Canada. Interpretation: The samples generated exclusively through advertising and respondent-driven sampling were not representative of the gold standard sample from the CCHS. Use of such biased samples for research studies could generate misleading results.

Énoncé de position commune sur la variable linguistique - Regroupement des Entités de planification des services de santé en français de l’Ontario (Réseau des services de santé en français de l’Est de l’Ontario, 2013)

Better data for better planning: The challenge of evidence-based data for sound planning of French-Language health services in Ontario - Réseau des services de santé en français de l’Est de l’Ontario (The challenge of evidence-based data for sound planning of French-Language health services in Ontario, 2013)

Des données pour mieux planifier: Le défi des données pertinentes pour une planification judicieuse des services de santé offerts en français en Ontario - Réseau des services de santé en français de l’Est de l’Ontario (Le défi des données pertinentes pour une planification judicieuse des services de santé offerts en français en Ontario, 2013)

Les variables linguistiques : un impératif pour une planification de services de santé adaptée aux besoins des francophones. État des lieux - Réseau des services de santé en français de l’Est de l’Ontario (État des lieux, 2012)

Recommandation du Réseau. Application pratique de la Définition inclusive de francophone (DIF) - Réseau des services de santé en français de l’Est de l’Ontario (Application pratique de la Définition inclusive de francophone (DIF), 2013)

Recommandation du Réseau. Collecte des données linguistiques - Réseau des services de santé en français de l’Est de l’Ontario (2016)

Réseau recommendation. Application of the Inclusive definition of Francophone (IDF) - Réseau des services de santé en français de l’Est de l’Ontario (Application of the Inclusive definition of Francophone (IDF), 2013)

Services en français dans les CLOSM : produire des données probantes pour améliorer l’accès et la qualité. Mémoire du Réseau des services de santé en français de l’Est de l’Ontario dans le cadre de la consultation sur le renouvellement du PCLOS 2013-2018 - Réseau des services de santé en français de l’Est de l’Ontario (2016)

Implementing the Evidence for Language-appropriate Health Care Systems: The Welsh Context - Roberts, Gwerfyl W.; Burton, Christopher R. (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Like Canada, Wales, UK is a bilingual nation: the Welsh language is an important part of its national identity and legislative framework. This has implications for the delivery of public sector services, particularly in the context of health and social care, where responding to the language needs of service users is fundamental to quality health care provision. Nevertheless, despite the strengthening policy commitment for a whole-system approach towards enhancing Welsh language services, there is a paucity of evidence to guide best practice in organizational planning in health care settings. This commentary outlines the context and significance of bilingual health care provision in Wales and the implications for building and embedding the evidence base. It calls for further work to translate our knowledge and understanding of language-appropriate practice to provide more effective and sensitive health care services; and to close the implementation gap between evidence and practice. Given the relevance of this challenge for health care providers in Canada who plan and deliver services for French-language minorities, this approach has resonance across our research communities. Thus, in our common pursuit to establish integrated knowledge translation research for language-appropriate health care systems, this commentary offers a focus for reflection, discussion and collaborative action. KEY WORDS: Knowledge management; language; minority health; organizational change; Wales

Assessment of validity for the “language spoken at home” variable in Québec death records: Summary. Language, determinant of health status and of services' quality - Trempe, Normand; Boivin, Marie-Claude; Lo, Ernest; Diogo Barry, Amado (Institut national de santé publique du Québec, 2012)

La validité de la variable « Langue d’usage à la maison » du Fichier des décès du Québec : synthèse. La langue, déterminant de l'état de santé et de la qualité des services - Trempe, Normand; Boivin, marie-claude; Lo, Ernest; Diogo Barry, Amado (Institut national de santé publique du Québec, 2012)